Nem heróis, nem vilões: o lugar dos diretores de povoações nas dinâmicas de transgressão à lei do diretório dos índios (1757-1798) - COELHO, Mauro Cezar (Universidade Federal do Pará, 2017)
This paper aims to understanding better the actions of villages' administrators - agents responsible for settled Indians' tutelage during the term of the Indians' Directory. We will highlight two issues. First, the socioeconomic universe of administrators in their workplaces, the indians' villages. Second, the historical character, and not moral, of transgressions committed by these subjects. This goal is because we consider limited the only vision formulated by historiography in relation to administrators: agents, because of their actions, that were decisive for the failure of the directory.